PENGARUH PENGENDALIAN INTERN KAS, FINANCIAL PRESSURE, KESESUAIAN KOMPENSASI, DAN MORALITAS INDIVIDU TERHADAP KECURANGAN (FRAUD) PADA LPD DI KECAMATAN TAMPAKSIRING GIANYAR - Erisianita Lestari Suprapta; Kadek Dewi Padnyawati (UNHI Press, 2021)
Fraud or commonly called fraud is a fraudulent act that is done intentionally to benefit one party (an individual, company or institution) unfairly or violates the law resulting in losses on the other party. This study aims to determine the effect of cash internal control, financial pressure, suitability of compensation, and individual morality for fraud. The population in this study were LPD employees throughout Tampaksiring Gianyar District. The number of respondents used was 63 peoples. The method used in determining the sample using the Slovin formula. Based on the results of this study indicate that financial pressure has a positive and significant effect on fraud, while internal cash control, suitability of compensation, and individual morality do not significantly influence fraud (fraud) in LPDs in Tampaksiring Gianyar District.